2014
DOI: 10.1103/physrevlett.112.218001
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Same-Material Tribocharging in Insulating Grains

Abstract: Observations of flowing granular matter have suggested that same-material tribocharging depends on particle size, typically rendering large grains positive and small ones negative. Models assuming the transfer of trapped electrons can account for this trend, but have not been validated. Tracking individual grains in an electric field, we show quantitatively that charge is transferred based on size between materially identical grains. However, the surface density of trapped electrons, measured independently by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
120
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 45 publications
6
120
1
Order By: Relevance
“…Thus, the particle tracking during freefall was essentially a diagnostic of the triboelectric or contact charging that had occurred during earlier particle-particle contacts, most likely inside the hopper during the outflow process. Waitukaitis et al (2013;2014) were able to show that such contact charging among particles made from the same material involves the transfer of negative charge and that the charging magnitude can be linked directly to the dispersion in particle size, as proposed earlier by Lacks et al (2007;2008). Particles smaller than the mean size tend to become charged negatively, while larger particles tend to acquire positive charge.…”
Section: Clusters and Cohesive Forcesmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the particle tracking during freefall was essentially a diagnostic of the triboelectric or contact charging that had occurred during earlier particle-particle contacts, most likely inside the hopper during the outflow process. Waitukaitis et al (2013;2014) were able to show that such contact charging among particles made from the same material involves the transfer of negative charge and that the charging magnitude can be linked directly to the dispersion in particle size, as proposed earlier by Lacks et al (2007;2008). Particles smaller than the mean size tend to become charged negatively, while larger particles tend to acquire positive charge.…”
Section: Clusters and Cohesive Forcesmentioning
confidence: 59%
“…We note that polarization forces are always attractive, irrespective of the charge polarity on the participating particles. For single-peaked particle size distributions, where the peak of the associated charge distribution from collisions will be near zero charge (Waitukaitis et al (2014), this means that clusters will tend to be comprised of (near) neutral particles that have aggregated around highly charged ones.…”
Section: Clusters and Cohesive Forcesmentioning
confidence: 99%
“…Past studies have largely focused on geometric or material differences between grains [13][14][15][16][17]. Remarkably, however, grains that are absolutely identical in shape, size and chemical composition have also been found to charge one another [16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This distribution is the result of a very large number of collisions and sliding/rubbing events among particles during sample preparation and outflow from the vessel 20 . It arises from tribocharging between grains of identical material, and thus statistically similar surface density of transferable charges, but slightly different surface area 9,21,22 . Overall charge is conserved and the distribution is centred around zero.…”
mentioning
confidence: 99%
“…In particular, for a bimodal P(q) with positive and negative peaks roughly symmetric around zero, we would expect typical cluster configurations in which contacting grains exhibit alternating polarity. Recent experiments have demonstrated that such a P(q) can be achieved by mixing bidisperse same-material grains 22 . The P(q) for such a mixture using diameters 326 ± 10 ”m and 251 ± 10 ”m is shown in Fig.…”
mentioning
confidence: 99%